Politeness and compassion differentially predict adherence to fairness norms and interventions to norm violations in economic games - Zhao, Kun; Ferguson, Eamonn; Smillie, Luke D. (Nature Publishing Group, 2017)
Adherence to norms and interventions to norm violations are two important forms of social behaviour modelled in economic games. While both appear to serve a prosocial function, they may represent separate mechanisms corresponding with distinct emotional and psychological antecedents, and thus may be predicted by different personality traits. In this study, we compared adherence to fairness norms in the dictator game with responses to violations of the same norms in third-party punishment and recompensation games with respect to prosocial traits from the Big Five and HEXACO models of personality. The results revealed a pattern of differential relations between prosocial traits and game behaviours. While norm adherence in the dictator game was driven by traits reflecting good manners and non-aggression (i.e., the politeness aspect of Big Five agreeableness and HEXACO honesty-humility), third-party recompensation of victims—and to a lesser extent, punishment of offenders—was uniquely driven by traits reflecting emotional concern for others (the compassion aspect of Big Five agreeableness). These findings demonstrate the discriminant validity between similar prosocial constructs and highlight the different prosocial motivations underlying economic game behaviours.